Silent surfaces : an experience in Portugal - Freitas, Elisabete F. (2008)
It is acknowledged that traffic noise affects human behaviour and health. Measures aiming at mitigating the impact of traffic noise are not always viable in urban areas. In Portugal, road designers have recently started to consider silent surfaces as alternative within their road pavement projects. In this paper the tire-surface noise of three surface layers integrated in a rehabilitation project carried out in an urban road that carries more than 40000 vehicles per day is assessed: i) one dense asphalt layer with limited maximum aggregate size, following the SILVIA recommendations for low noise surfaces; ii) two very-thin surfaces with different grading, which are an adaptation of the very-thin layers widely used in France to Portuguese conditions. The surface layers were constructed consecutively, involving segment lengths with more than 500 m. The surface texture was measured using a high speed profilometer. Skid resistance was also measured. The noise level was measured both by pass-by tests with selected traffic (trucks and light vehicles) at several speeds and by close proximity tests. The thin layers tested provided very good noise reduction values, especially at high speeds, and had a better performance than gap graded asphalt rubber surfaces frequently used in Portugal.